Differences in auditory brainstem responses between laboratory-reared and wild-caught prairie voles (Microtus ochrogaster) - Luberson Joseph; Naleyshka Colon-Rivera; Emily M. New; Desi M. Joseph; Jessica A. Hurd; Casey E. Sergott; Elizabeth A. McCullagh (PLoS ONE, 2026)
Prairie voles ( Microtus ochrogaster ) are a semi-fossorial rodent that are an emerging model in social neuroscience. Comparing laboratory-reared and wild-caught individuals is essential for understanding how environmental history shapes neural and sensory traits and for assessing the ecological validity of laboratory findings. Despite this, relatively few studies have taken this approach. We used auditory brainstem responses (ABRs) to compare ABR thresholds and ABR wave characteristics between laboratory-reared and wild-caught prairie voles. ABR recordings show that, similar to other semi-fossorial rodents, M. ochrogaster exhibit a hearing range of 1–46 kHz with peak sensitivity between 8–24 kHz in wild-caught and 8–32 kHz in laboratory-reared voles. However, wild-caught prairie voles displayed significantly lower ABR thresholds at 1, 4, 8, 16, and 24 kHz compared to laboratory-reared prairie voles. There were significant differences in interpeak latency between both tested groups, with laboratory-reared prairie voles showing faster interpeak latency responses than wild-caught voles. However, there were no differences in amplitude ratios between groups. Laboratory-reared prairie voles showed faster normalized latencies and higher relative amplitude of the binaural interaction component (BIC) of the ABR than wild-caught voles. There were no significant differences in ABR thresholds, interpeak latency, amplitude ratio, normalized latency, and relative amplitude between the sexes. These differences in auditory processing support the importance of integrating both wild and captive populations to advance comparative auditory research.